Mutation in a heterochromatin-specific chromosomal protein is associated with suppression of position-effect variegation in Drosophila melanogaster. - Eissenberg, J C (1990)
We report here that a point mutation in the gene which encodes the heterochromatin-specific nonhistone chromosomal protein HP-1 in Drosophila melanogaster is associated with dominant suppression of position-effect variegation. The mutation, a G-to-A transition at the first nucleotide of the last intron, causes missplicing of the HP-1 mRNA. This suggests that heterochromatin-specific proteins play a central role in the gene suppression associated with heterochromatic position effects.